Pertambangan Emas Tanpa Izin (Peti), Dampak Lingkungan, Sosial dan Ekonomi Serta Peranan Hukum Lingkungan di Kabupaten Lebong, Provinsi Bengkulu. - Muhammad Melian; Pico Pudiansa; Gumanti, Rokky; Reflis, Reflis; Satria P. Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Unlicensed gold mining in Lebong Regency, Bengkulu Province, is a complex problem with significant environmental, social and economic impacts. Unlicensed gold mining in Lebong Regency, Bengkulu Province, is a complex problem with significant environmental, social and economic impacts. This research aims to analyze the social interaction patterns of the illegal workers in the region. illegal workers in the region. The research method was conducted by analyzing and description of the social interaction patterns of mine workers, with a focus on the subject of illegal miners in Lebong Tambang Village, North Lebong Regency. Sample The sample consisted of 100 illegal miners with probability sampling technique. Sampling technique. Research variables include environmental impacts andenvironmental and health impacts caused by unlicensed gold mining activities. Instruments The instruments used were surveys, interviews and documentation, with qualitative and quantitative data analysis. The data analysis used is qualitative and quantitative data analysis. The research results are expected to provide input for stakeholders, especially local governments, in formulating sustainable management of natural resources and the environment. sustainable management of natural resources and the environment. This research is expected to provide input for stakeholders, especially local governments, in formulating sustainable management of natural resources and the environment. This research is also expected to be a reference material for research and development on the topic in the future. Thus, this research As such, this research contributes to reducing the risk of environmental damage and pollution caused by illegal mining practices in Lebong District. caused by illegal mining practices in Lebong Regency.